Is procedural memory enhanced in Tourette syndrome? Evidence from a sequence learning task. (March 2018) - Takács, Ádám; Kóbor, Andrea; Chezan, Júlia; Éltető, Noémi; Tárnok, Zsanett; Nemeth, Dezso; Ullman, Michael T.; Janacsek, Karolina
Abstract: Procedural memory, which is rooted in the basal ganglia, underlies the learning and processing of numerous automatized motor and cognitive skills, including in language. Not surprisingly, disorders with basal ganglia abnormalities have been found to show impairments of procedural memory. However, brain abnormalities could also lead to atypically enhanced function. Tourette syndrome (TS) is a candidate for enhanced procedural memory, given previous findings of enhanced TS processing of grammar, which likely depends on procedural memory. We comprehensively examined procedural learning, from memory formation to retention, in children with TS and typically developing (TD) children, who performed an implicit sequence learning task over two days. The children with TS showed sequence learning advantages on both days, despite a regression of sequence knowledge overnight to the level of the TD children. This is the first demonstration of procedural learning advantages in any disorder. The findings may further our understanding of procedural memory and its enhancement. The evidence presented here, together with previous findings suggesting enhanced grammar processing in TS, underscore the dependence of language on a system that also subserves visuomotor sequencing.